Labour market entry of non-labour migrants-Swedish evidence - Olof Åslund; Anders Forslund; Linus Liljeberg (Institute for Evaluation of Labour Market and Education Policy (IFAU), 2017)
We describe the short- and long-term patterns of labour market entry and integration among Non-Western, predominantly non-labour, immigrants to Sweden. Our main sample considers the 1990-2014 period. The patterns of time to first contact and labour market entry vary with business cycle conditions, country of origin and other background characteristics. But the main message is the remarkable stability of a relatively slow entry process and long-term outcomes below those of the average worker. The number of jobs before the "first real job" (entry) is limited and the first employer contact is for many a port to a more stable position. First jobs are comparatively often found in small, low-wage firms, which over time have become increasingly present in service industries. Our discussion of policy experiences suggests several margins and factors affecting the labour market outcomes of recent migrants, but also indicates that no single reform or measure is likely to in itself radically change the patterns.
Keywords: J61; J68; 330; Immigration; labour market entry; integration policy